2017
DOI: 10.1093/gerona/glx223
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Is Negatively Related to High Gravitational Impacts Achieved From Day-to-day Physical Activity

Abstract: BackgroundSarcopenia has been associated with reduced physical activity (PA). We aimed to determine if sarcopenia, and specific components of muscle size, function, and physical performance, are associated with high impacts achieved during habitual PA, as these are related to bone strength in community-dwelling older women.MethodsParticipants were older women from the Cohort of Skeletal Health in Bristol and Avon. We defined sarcopenia using the EWGSOP criteria. Lower limb peak muscle power and force were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…We recently demonstrated the feasibility and acceptability of using jumping mechanography to assess lower limb muscle function in a sample of community-dwelling women aged over 70 years old after first excluding women with significant frailty based on their Short Physical Performance Battery (SPPB) score [ 11 ]. We subsequently used jumping mechanography estimates to identify lower limb peak muscle force as well as gait speed as two independent predictors of osteogenic impacts in this age group [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated the feasibility and acceptability of using jumping mechanography to assess lower limb muscle function in a sample of community-dwelling women aged over 70 years old after first excluding women with significant frailty based on their Short Physical Performance Battery (SPPB) score [ 11 ]. We subsequently used jumping mechanography estimates to identify lower limb peak muscle force as well as gait speed as two independent predictors of osteogenic impacts in this age group [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given sex differences in use of elastic energy [ 21 ] and body composition it is also conceivable that male and female responses to power events and related training may differ. In addition, older women tend to undertake less vigorous physical activity, known to be beneficial for muscle function[ 22 ], than older men [ 23 ]. Therefore, whilst absolute training volume was similar in athletes of both sexes, this may represent a greater departure from habitual activity levels in female than male athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerometers provide an opportunity, with minimal additional participant burden, to examine physical activity beyond these simple metrics. In this issue, researchers used accelerometers to examine physical activity patterns, looking closely at "how" physical activity is accrued over the course of the day (7,8), gait and balance (9), and how the mechanical forces of activity such as vertical impacts experienced during activity (10,11).…”
Section: Moving Beyond a Single Physical Activity Metricmentioning
confidence: 99%
“…Expanding on previous literature showing that vertical impact (the force applied in the upward or downward direction due to activity) is positively associated with bone mineral density (18,19), two studies, one by Hartley and colleagues and the other by Elhakeem and colleagues, used a hip-worn accelerometer to measure vertical impacts over 7 days among community-dwelling older women to examine the association of vertical impact intensity with sarcopenia and body composition (10,11). Both Elhakeem and colleagues and Hartley and colleagues observed that high-intensity impacts, but not lower-or moderate-intensity impacts, were associated with sarcopenia and body composition (10,11).…”
Section: Focusing On Aging Outcomesmentioning
confidence: 99%
See 1 more Smart Citation